Organic Field‐Effect Transistors: The Origin of Excellent Gate‐Bias Stress Stability in Organic Field‐Effect Transistors Employing Fluorinated‐Polymer Gate Dielectrics (Adv. Mater. 42/2014). (November 2014) - Kim, Jiye; Jang, Jaeyoung; Kim, Kyunghun; Kim, Haekyoung; Kim, Se Hyun; Park, Chan Eon
<x xml:space="preserve">Abstract</x> The energy barrier for charge transfer at a semiconductor and dielectric interface can be tuned by varying the dielectric functionality, as described by S. H. Kim, C. E. Park and co‐workers on page 7241. On the right side, the higher‐energy barrier of the fluorinated polymer dielectric reduces the escaped and trapped carriers from the channel region to the dielectric surface. The lower‐energy barrier of the polymer dielectric on left side induces a large amount of escaped and trapped charge at the dielectric surface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>